(untitled) (Cadernos de Sociomuseologia, 2019)
The presentation discusses possibilities of strategic action to the Inhotim Museum, located in the state of Minas Gerais, in Brazil, focusing in a sustainable process to further develop the institution. Those proposals are constructed from three broad concepts: the museum, sustainability and strategy, with the balance between those three dimensions as the key for all the process. Keywords: Inhotim Museum, sustainability, strategy